PENETAPAN KESADAHAN TOTAL (CaCO3) AIR SUMUR DI DUSUN CEKELAN KEMUSU BOYOLALI DENGAN METODE KOMPLEKSOMETRI - Astuti, Dian Wuri; Rahayu, Muji; Rahayu, Dewi Sri (Universitas Ahmad Dahlan, 2015)
Background: Water is a basic requirement for human life, both in terms of quantity and quality have not been fulfilled can have a large impact on the problems that are often found in water service that the quality of groundwater and river water used by the people who are less qualified as clean water even in some places even unfit for use. One of the chemical parameters in terms of water quality is the number of the element content of Mg2+ and Ca2+ in the presence of water commonly called water hardness. Hardness in water is not desired either for domestic use or for industrial use. This study aims to determine the total hardness of water wells in the village Cekelan District of Kemusu Boyolali, whether in accordance with PERMENKES RI 416/Menkes/PER/IX/1990 on water quality standards. Methods: This was a descriptive observational study. The sample under study is taken directly from the existing wells in the village Cekelan random as many as 44 samples. Laboratory tests by the titration method complexometry. Results: The total hardness (CaCO3) water wells that have been examined is 2.0 mg/L to 520 mg/L. Conclusion: Total hardness (CaCO3) water wells in village Cekelan Kemusu Boyolali indicates that there are 11,36% samples were ineligible and 88,64% samples qualify.Â Keywords: Total hardness (CaCO3), Water well, Complexometry